Benefits realization management : a practice guide (Project Management Institute, 2019)
Providing a comprehensive look at the topic of benefits realization in of portfolio, program, and project management, this practice guide will help readers tackle this important topic and drive more successful outcomes and better strategic alignment in your organization. --